Spatial Ecology of Sub-Adult Green Turtles in Coastal Waters of the Turks and Caicos Islands: Implications for Conservation Management - Philip D. Doherty; Annette Cameron Broderick; Brendan John Godley; K. A. Hart; Q. Phillips; A. Sanghera; Thomas B. Stringell; J. T. Walker; Peter Bradley Richardson (Frontiers in Marine Science, 2020)
Marine turtles are of conservation concern throughout their range, with past population declines largely due to exploitation through both legal and illegal take, and incidental capture in fisheries. Whilst much research effort has been focused on nesting beaches and elaborating migratory corridors, these species spend the vast majority of their life-cycle in foraging grounds, which are, in some species, quite discrete. To understand and manage these populations, empirical data are needed on distribution, space-use, and habitats to best inform design of protective measures. Here we describe space-use, occupancy, and wide-ranging movements derived from conventional flipper tagging and satellite tracking of sub-adult green turtles (Chelonia mydas) within the coastal waters of the Turks and Caicos Islands (TCI; 2011–2017). 623 turtles were fitted with flipper tags, with 69 subsequently recaptured, five of which in international waters. Sixteen individual turtles of between 63 and 81 cm curved carapace length were satellite tracked for a mean 226 days (range: 38–496). Data revealed extended periods of occupancy in the shallow coastal waters within a RAMSAR protected area. Satellite tracking and flipper tagging showed wide-ranging movements, with flipper tag recaptures occurring in waters off Nicaragua (n = 4), and Venezuela (n = 1). Also, four of 16 satellite tracked turtles exhibiting directed movements away (displaced >450 km) from TCI waters traveling through nine geo-political zones within the Caribbean-Atlantic basin, as well as on the High Seas. One turtle traveled to the Central American coast before settling on inshore habitat in Colombia’s waters for 162 days before transmission ceased, indicating ontogenetic dispersal to a distant foraging habitat. These data highlight connectivity throughout the region, displaying key linkages between countries that have previously only been linked by genetic evidence. This study also provides evidence of the importance of the Turks and Caicos Islands marine protected area network and importance of effective management of the sea turtle fishery for regional green turtle populations.